Immune checkpoint blockade with anti-programmed cell death 1 (PD-1) monoclonal antibody (mAb) cemiplimab: ongoing and future perspectives in rare genital cancers treatment. Issue 1 (31st January 2022) - Gambale, Elisabetta; Fancelli, Sara; Caliman, Enrico; Petrella, Maria Cristina; Doni, Laura; Pillozzi, Serena; Antonuzzo, Lorenzo
Abstract : Cemiplimab is a highly potent, hinge-stabilized human IgG4 monoclonal antibody (mAb) targeting programmed cell death 1 (PD-1) receptor approved for patients with locally advanced or metastatic cutaneous squamous cell carcinoma (SCC) who are not candidates for curative surgery or curative radiation. Recently, the phase 3 trial EMPOWER-Cervical 1 has investigated cemiplimab in patients with recurrent/metastatic cervical cancer. At interim analysis, overall survival (OS), progression free survival (PFS) and objective response rate (ORR) in overall and SCC populations favored cemiplimab over single agent chemotherapy. Cervical SCCs are the first for incidence among Human Papilloma Virus (HPV) related neoplasms and are highly correlated (about 95%) with the viral infection. Similarly, penile and vulvar SCC may develop on chronic HPV infections or on dermatological chronic conditions (ie, lichen). The molecular and viral similarities between external genital SCC and SCC originating from the cervical epithelium could be the rationale for using cemiplimab to treat locally advanced or metastatic penile and vulvar SCC as well. Some retrospective data have shown that cemiplimab may provide objective response and clinical benefit to some patients with penile or vulvar SCC and is overall safe to utilize in this population. Given the complexity of the immune activation and the considerable variability in tumor biology across patients and tumor types, the identification of biomarkers to warrant patient selection needs to be further explored. Ongoing clinical trials will hopefully shed light on the treatment paradigm of these rare tumors too, with special regard to the ideal combination and sequencing of immunotherapeutic strategies.